Estudio comparativo de la percepción estética del odontólogo sobre el diseño de sonrisa utilizando dos métodos para determinar la proporción dental - Oruna Abanto, Roald Boris (2015)
The aim of this comparative descriptive, transversal and observational research was compare the level of aesthetic perception between the design of smile based on Chu´s Method and golden proportion by dentists. The sample had 35 dentists (who are in a diploma in restorative and cosmetic dentistry in USEE), they saw 4 front photos of smile (2 of women and 2 of men). Photos were manipulated by image editing software Adobe Photoshop version 14.2.2 to change dental proportions based on golden proportion and Chu´s method. The value of aesthetic perception was determined by a visual analog scale. The result was that dentists had a better aesthetic perception of smile designed based on Chu´s proportion in female patients (p<0.05). However, the design of smile in male patients didn´t show statistically significant difference between both methods (p>0.05). The conclusion was that dentist had different aesthetic perception for design of smile based on golden proportion and based on Chu´s proportion